Systematic Literature Review: Exploring Antecedents And Consequences Of Spiritual Leadership - Wadud, Abdul; Agustina, Tri Siwi (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2024)
This study conducted a systematic literature review on spiritual leadership in an organizational context. From 539 articles identified through the Scopus database, 21 articles were selected based on the criteria of year of publication, relevance to business management and accounting, and the keyword "spiritual leadership." Results show that antecedents of spiritual leadership include core values such as shared vision and altruistic love, while consequences include improved performance, employee engagement, innovation, as well as reduced workplace exclusion. Spiritual leadership also increased organizational commitment and citizenship behaviour (OCB) through the mediation of workplace spirituality and job satisfaction. This study concludes that spiritual leadership plays an important role in creating an inclusive and supportive work environment, as well as improving employee well-being and innovation. A recommendation for future research is to explore the application of spiritual leadership in various industry contexts.